Strategi inovasi digital dalam meningkatkan daya saing perbankan syariah di indonesia pada era transformasi keuangan - Mayang, Endang (Maliki Interdisciplinary Journal, 2025)
The development of digital technology in the financial sector has been a major driver of increased efficiency, inclusiveness, and competitiveness of financial institutions, including sharia-based banks. This study focuses on analyzing the digital innovation strategies implemented by Islamic banks in Indonesia in facing the challenges of global financial transformation. The research approach used is descriptive qualitative through literature review and analysis of secondary data sourced from Islamic bank financial reports, publications from the Financial Services Authority (OJK), and previous research results during the period 2020–2025. The research findings indicate that the application of digital innovation, such as the development of Islamic mobile banking applications, the use of artificial intelligence (AI) to improve customer service, and the integration of digital payment systems in accordance with Islamic principles, contributes significantly to improving operational efficiency and expanding market access. In addition, strategic partnerships with Islamic fintech and the implementation of the open banking concept are important steps to strengthen the competitive position of Islamic banking against conventional banks. However, there are a number of challenges such as data security, low digital literacy, and the adjustment of innovations to Islamic principles. This research confirms that the success of digital transformation in the Islamic banking sector is largely determined by collaboration between the implementation of digital innovation and the adaptation of Islamic principles. This study emphasizes that the success of digital transformation in the Islamic banking sector is largely determined by the collaboration between innovation strategies